FORMULASI DAN UJI EVALUASI SEDIAAN SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) DARI EKSTRAK METANOL AKAR PANDAN LAUT (PANDANUS ODORIFER) - Ghiffari, Habibie Deswilyaz; Suhendra, Arif; Vonikartika, Arie; Roza Erda (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2025)
Background: Pandanus odorifer is a coastal plant in Southeast Asia with roots rich in bioactive compounds such as phenolics, flavonoids, saponins, and alkaloids. Limited solubility and bioavailability of lipophilic compounds hinder therapeutic effectiveness. Objective: To develop and evaluate Self-Nanoemulsifying Drug Delivery System (SNEDDS) formulation from sea pandanus root methanol extract to enhance solubility and stability. Methods: Root extraction was performed using soxhlet method with methanol solvent. Six SNEDDS formulas were developed with variations of Tween 80/Tween 20 surfactant combinations and PEG 400/propylene glycol cosurfactants. Evaluation included simplicia characterization, organoleptic tests, creaming tests, pH and viscosity measurements, centrifugation, freeze-thaw stability, solubility, and droplet size analysis. Results: Extract yield reached 7.72% with simplicia characterization meeting pharmacopoeial standards. Formula F3 (Tween 80 21.4%, PEG 400 21.4%, VCO 4.75%, extract 5%) demonstrated optimal stability with pH 6.91±0.04, viscosity 253.33±11.55 cPs, HLB value 14.50, and average droplet size 530 nm. This formula maintained homogeneity throughout all stability tests without phase separation. Conclusion: SNEDDS from Pandanus odorifer root methanol extract formula F3 possesses physicochemical characteristics and stability suitable for nanoemulsion-based drug delivery systems.